2009
DOI: 10.4028/www.scientific.net/kem.410-411.263
|View full text |Cite
|
Sign up to set email alerts
|

Process Variables Optimisation of Polypropylene Based Fibre-Metal Laminates Forming Using Finite Element Analysis

Abstract: This study investigates the effect of preheat temperature, blank holder force and feed rate on the formability of polypropylene based Fibre-Metal Laminates. Finite element method combined with Design of Experiments was used to determine the influence of the forming process parameters. The design of experiments was used to identify the relative influence of each process parameter considered in this study. A reduced set of coupled structural-thermal simulations using Ls-Dyna were carried out using a L9 orthogona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The authors investigated the effect of changes in the coefficient of friction between 0.1 and 0.3 on blank holder intensity during the forming of a non-symmetrical draw piece. Dharmalingam et al [31] used the statistical experiments and finite element method to determine the influence of the parameters of the forming process of 2/1-aluminium/composite consisting of two layers of comingled 2:2 twill weave glass-fibre/polypropylene composite prepreg and annealed EN AW-5005-H34 aluminium sheets. The coefficient of friction between the FML blank and the forming tools was arbitrarily assumed to be constant with a value of 0.031.…”
Section: Introductionmentioning
confidence: 99%
“…The authors investigated the effect of changes in the coefficient of friction between 0.1 and 0.3 on blank holder intensity during the forming of a non-symmetrical draw piece. Dharmalingam et al [31] used the statistical experiments and finite element method to determine the influence of the parameters of the forming process of 2/1-aluminium/composite consisting of two layers of comingled 2:2 twill weave glass-fibre/polypropylene composite prepreg and annealed EN AW-5005-H34 aluminium sheets. The coefficient of friction between the FML blank and the forming tools was arbitrarily assumed to be constant with a value of 0.031.…”
Section: Introductionmentioning
confidence: 99%
“…Kalyanasundaram et al [26] showed that the use of high temperature in the forming process of FMLs with the thermoplastic base, melts the base material and in the deformation process, the layers slip over each other. DharMalingam et al [27], using finite element simulations, showed that the optimum temperature for achieving the highest FMLs formability with PP base is 130˚C. Valizadeh et al [28].conducted an experimental investigation on L-die bending of UNS C10100 copper/aluminum 1100 two layers' sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Forming of thermoplastic FML systems has primarily been investigated using draw and cup forming [9][10][11][12][13][14]. Gresham et al showed that the blank holder force significantly affects the formability of the laminate.…”
Section: Introductionmentioning
confidence: 99%